An anthology of contemporary ecotheology, philosophy and eco-justice practices - Furlan-Štante, Nadja 1974-; Andrianos, Lucas A.; Bredal-Tomren, Tom Sverre 1966- (ECOTHEE, 2023)
The articles selected in this seventh volume, ECOTHEE 22, continue the development of ecotheological resources on environmental ethics and sustainable solutions for the common oikos. This book follows the ECOTHEE goal and seeks to engage theology on key ecological concerns from a variety of religious traditions and perspectives. The emphasis is on theological and ethical implications of contributing to a sustainable ecological future. This publication is enriched with additional articles from the 5th SAPREJ conference on sustainable alternatives to poverty reduction and eco-justice and the roles, responsibilities and initiatives of religion, science and civil societies for ecological justice and biodiversity protection, held in Addis Ababa, Ethiopia, in May 2023. /// The present ECOTHEE 22 book is structured into the following sections: Introduction, Section 1: Towards Reconciliation and Justice for all Creation (Eco-ethical Theological and Philosophical Reflections), Section 2: Governance, Politics, Good Practices, and Critical Evaluations of Ecological (In)Justice. /// An "Anthology of Contemporary Ecotheology, Philosophy and Eco-Justice Practices" volume of ECOTHEE delivers chapters on contemporary insights into various religious, spiritual, philosophical reflections towards reconciliation and ecojustice for a sustainable future